2013
DOI: 10.48550/arxiv.1310.0453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massive spin-2 theories

Abstract: We give an introduction to massive spin-2 theories and the problem of their non-linear completion. We review the Boulware-Deser ghost problem and two ways to circumvent classic no-go theorems. In turn, massive spin-2 theories are not uniquely defined. In the case of truncated theories, we show that the Boulware-Deser ghost may only be avoided if the derivative structure of the theory is not tuned to be Einsteinian.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…This possibility was explored in Refs. [230,307,229] where it was shown that in four dimensions, the following derivative interaction L (der) 3 is ghost-free at leading order (i.e., there is no higher derivatives for the Stückelberg fields when introducing the Stückelberg fields associated with linear diffeomorphism),…”
Section: No New Kinetic Interactionsmentioning
confidence: 99%
“…This possibility was explored in Refs. [230,307,229] where it was shown that in four dimensions, the following derivative interaction L (der) 3 is ghost-free at leading order (i.e., there is no higher derivatives for the Stückelberg fields when introducing the Stückelberg fields associated with linear diffeomorphism),…”
Section: No New Kinetic Interactionsmentioning
confidence: 99%
“…Repeating the procedure we followed at cubic order, we find the most general ghost free quartic lagrangian can be written in terms of five parameters: a, b 1 , and b 2 , as well as two new parameters c 1 and c 2 L (4) g.f.,Λ 3 = a L (2) a + L (3) a + L (4) a…”
Section: Quartic Ordermentioning
confidence: 99%
“…The Einstein-Hilbert term actually satisfies Property 2 trivially since the Stückelberg fields do not enter the full Einstein-Hilbert term, since it is covariant 4. This statement is more profound than it may seem: Requiring that no more than five degrees of freedom propagate in the kinetic term we deduce that only the Einstein-Hilbert term is acceptable, which is covariant and by itself only propagates two degrees of freedom.…”
mentioning
confidence: 97%
“…, since with this choice of α, β i explicitly appears linearly in the Hamiltonian when c 1 = 2c 5 (while with other values of λ, this degeneration is not transparent), which corresponds to the GR case. 5 More explicitly, in terms of (41), L GR which was identified in [20] (see also [18,19]).…”
Section: B Derivative Terms and The Compatible Potential Termsmentioning
confidence: 97%
“…In [18] (see also [19]), non-GR cubic self-interaction terms with two spacetime derivatives was shown to exist using the helicity decomposition. Such a possibility was systematically investigated in [20] in arbitrary dimensions and with more than two derivatives, where a class of so-called "pseudolinear" terms was identified.…”
Section: Introductionmentioning
confidence: 99%